Color related to ceramic and zirconia restorations: A review - Vichi, Alessandro; Louca, Chris; Corciolani, Gabriele; Ferrari, Marco (Dental materials, 2011)
The requirement to achieve natural looking restorations is one of the most challenging aspects of dentistry, and the shade matching of dental restorations with the natural dentition is a difficult task due to the complex optical characteristics of natural teeth. Dental porcelain is considered the reference material for prosthetic rehabilitation, but it is not easy to handle and aesthetic excellence is quite difficult to obtain. For these reasons, shade matching with dental porcelain is often considered to be more artistic than scientific. Shade matching is considered unpredictable due to several variables that may influence the final appearance of a restoration. In order to improve this situation, over the last decade new shade guides and instruments have been developed and the aesthetic aspects of dental porcelain have been further investigated. In this review some aspects of color selection and color reproduction have been examined. Color selection has advanced through the development of new shade guides and electronic shade taking devices, although visual assessment has still not been entirely replaced by electronic instruments. Color reproduction with dental porcelain has improved thanks to advances in the performance and knowledge of dental porcelain, but is still not easy to achieve. The difficulties of achieving good aesthetics with PFM restorations and the desire for metal free solutions have resulted in the increased use of zirconia. The unique optical properties of zirconia have introduced new opportunities for achieving superior aesthetics, however further research is required with this material.